Sources d'influence de l'engagement des étudiants dans un dispositif de classe inversée à l'université : le cas de PedagInnov - Laetitia Gerard; Ariadna Ayala Rubio
enThe project PedagInnov is an experimentation of the flipped classroom in higher education. It is part of a ministerial educational project Individualisation, diversification, evaluation and mentoring (IDEA), which has been developed since 2012 by the COMUE of the University Paris-Est. Ten academics have accepted to change their traditional courses into flipped classrooms. We have focused on the following question: how could we encourage students' engagement in an educational innovation such as the flipped classroom? To answer the question, we interviewed 13 students and 7 academics who have chosen to test the flipped classroom. We have identified three main sources of implication of students: the posture of the mentor teacher, resources and supports, and evaluation.